2017
DOI: 10.1155/2017/8348390
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Global Assessment and Handgrip Strength as Predictive Factors in Patients with Liver Cirrhosis

Abstract: Background and Aims Malnutrition is common in patients with chronic liver disease. We aimed to evaluate malnutrition assessment tools in predicting severity and survival of patients with liver cirrhosis. Material and Methods We examined patients with liver cirrhosis. Nutritional evaluation was performed on admission, using subjective global assessment (SGA), handgrip strength (HGS), and anthropometry. Patients were followed up for 6 months. Results We included 100 patients, 72 men, with mean age of 59.2 years.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
43
1
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 21 publications
9
43
1
3
Order By: Relevance
“…Despite these differences, sarcopenia by each of the 3 techniques correlated with wait‐list mortality. Previously published studies demonstrating such a link have examined the 6‐Minute Walk Test, handgrip strength, short physical performance battery, subjective global assessment, psoas muscle thickness on CT, transverse muscle area on CT, and DEXA LM measures . This study is unique in its analysis of different diagnostic methods in a single cohort of patients with most previous studies employing single‐slice CT scans at the L3 level …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these differences, sarcopenia by each of the 3 techniques correlated with wait‐list mortality. Previously published studies demonstrating such a link have examined the 6‐Minute Walk Test, handgrip strength, short physical performance battery, subjective global assessment, psoas muscle thickness on CT, transverse muscle area on CT, and DEXA LM measures . This study is unique in its analysis of different diagnostic methods in a single cohort of patients with most previous studies employing single‐slice CT scans at the L3 level …”
Section: Discussionmentioning
confidence: 99%
“…Given the superiority of the MELD–handgrip strength predictive model, handgrip strength may therefore be the most appropriate diagnostic tool to improve clinical decision making in patients with cirrhosis. It can be performed at the bedside or during an outpatient consultation in a matter of minutes without additional risk or cost and has been well validated in previous cirrhotic populations as a predictor of mortality …”
Section: Discussionmentioning
confidence: 99%
“…Meta‐analysis: Twenty‐two studies with a total of 4057 were meta‐analysed with a combined increased RR of pre‐transplant mortality in those patients who were malnourished vs not of 2.38 (95% CI 1.96‐2.89, I 2 55%) (Figure ) . When separated by individual NATs, similar results were seen (Table ).…”
Section: Resultsmentioning
confidence: 62%
“…The search was repeated on February 14, 2018, restricted to articles published since August 5, 2017. Sixty‐three further abstracts yielded 12 articles for full‐text review and 6 articles which could be included in the study . Only four of these articles had data which could be meta‐analysed .…”
Section: Resultsmentioning
confidence: 99%
“…This limitation of SGA can be overcome by concomitant use of handgrip strength (HGS) with the use of a dynamometer. One recent study showed that the SGA and HGS corelated with the severity of liver disease, as predicted by Child‐Pugh and Model for End Stage Liver Disease (MELD) scores that were statistically significant …”
Section: Assessment Of Malnutrition In Cirrhosismentioning
confidence: 98%